A TRIGONOTARBID ARACHNID FROM THE UPPER CARBONIFEROUS OF THE SAN GIORGIO BASIN, SARDINIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A trigonotarbid arachnid from the Upper Carboniferous (Westphalian D) of San Giorgio Basin, Sardinia, is described and referred to Anthracomartus voelkelianus Karsch, 1882, the type genus of the family Anthracomartidae. The occurrence extends the range of this arachnid order outside of the major Euramerican coal basins and into the western Mediterranean region. This is the first pre-Miocene arachnid from Italy to be described.
Keywords: Anthracomartidae; Westphalian; Sardinia